The bibliometric analysis of the studies conducted in the field of water buffalo breeding: The bibliometric analysis of water buffalo breeding - Celik, Senol (Progress in Nutrition, 2021)
Summary. Purpose: The aim of the study is to examine nearly 500 studies published between the years 2013-2019 in the field of water buffalo breeding in bibliometric terms and to reveal the tendencies and trends in the field in recent years. Methods: A review has been performed on the titles “buffalo” in Web of Science Core Collection database and bibliometric data were accessed regarding the studies. The current issues regarding the concept of water buffalo breeding were revealed in order to contribute to the academicians and researchers studying on water buffalo breeding. Results: The studies were examined within the context of the number of publications by years, types of publication, reference analyses, country cooperation and common reference webs. In addition, social web analysis was used regarding the determination of references, authors and keywords and references, country and keywords tendencies. According to the results of the analysis, Theriogenology is the journal with the highest h index and g index values from the journal publishing in the field of buffalo breeding. The journal with the highest number of publications on water buffalo breeding is Buffalo Bulletin with 138 studies. The countries where the highest number of articles were written in this field were India, Brazil and Pakistan whereas the countries with the highest number of references were India, Italy and Pakistan. The authors with the highest number of articles were found to be Chakravarty AK, Baabr ME, Kumar S, Nadeem A and Kataria RS respectively. It was also determined that the journals mostly referred to were Theriogenology, J. Dairy Sci. and Anim. Reprod Sci. respectively. Conclusion: As a results, the increase in bibliometrics studies can provide an important contribution by serving as a lead to the studies conducted in the field of husbandry.